Importance performance analysis for destination attributes development of tourism village - Nova Eviana; Rudhi Achmadi (Jurnal Pariwisata Pesona, 2022)
Segarajaya Village, located in Bekasi Regency, West Java, lacks optimal management of tourist destination attributes, which drives tourist satisfaction. Therefore, this research is crucial to consider the importance of fulfilling tourist satisfaction in encouraging tourist re-visits. The purpose of the study was to determine the level of tourist satisfaction with the attributes of the tourist attraction of Segarajaya Village. The method was quantitative research with IPA analysis by comparing the level of service importance and performance. Data collected using questionnaires includes six attributes; attractions, accommodation and food services, facilities, reputation, social component, and economy. About 110 tourists participated as respondents. The results showed that tourists consider accommodation and social components very important but perform poorly. Hence, it requires the participation of all stakeholders of Segarajaya Tourism Village to provide accommodation services (homestays) that meet hygiene and comfort standards, improve the hospitality and concern of local communities, as well as professional management, to realize the principles of community-based tourism.